The effect of surface charge on oral absorption of polymeric nanoparticles. (7th February 2018) - Du, Xiao-Jiao; Wang, Ji-Long; Iqbal, Shoaib; Li, Hong-Jun; Cao, Zhi-Ting; Wang, Yu-Cai; Du, Jin-Zhi; Wang, Jun
Abstract : Positively charged nanoparticles showed a favorable distribution in the small intestine, and significantly improved oral bioavailability. Abstract : Surface charge plays an important role in determining the interactions of nanoparticles with biological components. Substantial studies have demonstrated that surface charge affects the fate of nanoparticles after intravenous administration; however, few studies have investigated the effect of surface charge on the bioavailability and absorption of nanoparticles after oral administration. In this study, polymeric nanoparticles with a similar particle size and surface polyethylene glycol (PEG) density, but with varying surface charges (positive, negative and neutral), were developed to study the effect of surface charge on the oral absorption of polymeric nanoparticles. The nanoparticles were constructed from polyethylene glycol- block -polylactic acid (PEG-PLA) with the incorporation of lipid components with different charges. Our results suggested that the positive surface charge facilitated the cellular uptake and transport of nanoparticles through both Caco-2 cells in vitro and small intestinal epithelial cells in vivo . The positively charged nanoparticles showed a favorable distribution in the small intestine, and significantly improved the oral bioavailability. This study presents valuable information towards the design of nanoparticles for improved oral drug delivery.